High-intensity focused ultrasound therapy for pediatric and adolescent vulvar lichen sclerosus - Sili He; Jianfa Jiang (International Journal of Hyperthermia, 2022)
Objective The study’s objective was to retrospectively evaluate the efficacy and safety of high-intensity focused ultrasound (HIFU) for vulvar lichen sclerosus (VLS) in pediatric and adolescent patients.Methods Pediatric and adolescent patients presenting to our hospital from June 2007 to July 2021, with VLS were retrospectively evaluated. The participants’ information, including age, symptoms and vulvar examination, were documented, and they were treated with HIFU. The effectiveness of HIFU and its complications were analyzed.Results A total of 36 patients with VLS undergoing HIFU for whom complete follow-up data were available participated in the study. The mean age of the patients at diagnosis was 13.3 ± 4.1 years. All patients successfully underwent HIFU therapy. The mean sonication time was 20.3 ± 8.6 min, and the median treatment energy was 3579.0 J. A few blisters developed in 8 (22.2%) patients and 2 (5.6%) had ulcers. The skin burns were treated medically without scar formation. On average, patients were followed up for 52.0 months after the procedure (a range of 6–175 months). At 6 months after therapy, the total response rate was 91.6%, and 86.6% at 12 months post HIFU. Overall, 16 patients were followed up for more than 5 years. The total response rate was 75%, and the recurrence rate was 12.5%.Conclusions Based on our results, HIFU was demonstrated to be effective and relatively safe for the treatment of VLS in pediatric and adolescent patients, but it is necessary to pay attention to the possible skin burns.